Comparative transcriptome analysis reveals novel insights into transcriptional responses to phosphorus starvation in oil palm (Elaeis guineensis) root - Kong, Sze Ling; Abdullah, Siti Nor Akmar; Ho, Chai Ling; Musa, Mohamed Hanafi; Yeap, Wan Chin (BioMed Central, 2021)
Background: Phosphorus (P), in its orthophosphate form (Pi) is an essential macronutrient for oil palm early growth development in which Pi deficiency could later on be reflected in lower biomass production. Application of phosphate rock, a non-renewable resource has been the common practice to increase Pi accessibility and maintain crop productivity in Malaysia. However, high fixation rate of Pi in the native acidic tropical soils has led to excessive utilization of P fertilizers. This has caused serious environmental pollutions and cost increment. Even so, the Pi deficiency response mechanism in oil palm as one of the basic prerequisites for crop improvement remains largely unknown. Results: Using total RNA extracted from young roots as template, we performed a comparative transcriptome analysis on oil palm responding to 14d and 28d of Pi deprivation treatment and under adequate Pi supply. By using Illumina HiSeq4000 platform, RNA-Seq analysis was successfully conducted on 12 paired-end RNA-Seq libraries and generated more than 1.2 billion of clean reads in total. Transcript abundance estimated by fragments per kilobase per million fragments (FPKM) and differential expression analysis revealed 36 and 252 genes that are differentially regulated in Pi-starved roots at 14d and 28d, respectively. Genes possibly involved in regulating Pi homeostasis, nutrient uptake and transport, hormonal signaling and gene transcription were found among the differentially expressed genes. Conclusions: Our results showed that the molecular response mechanism underlying Pi starvation in oil palm is complexed and involved multilevel regulation of various sensing and signaling components. This contribution would generate valuable genomic resources in the effort to develop oil palm planting materials that possess Pi-use efficient trait through molecular manipulation and breeding programs.